Teste cometa: validação do método e avaliação da exposição ocupacional ao benzeno presente na gasolina através dos biomarcadores de exposição e genotoxicidade - Maria Augusta Amaral Campos (2013)
Through contact with gasoline, gas station attendants and analysts fuels are exposed to various volatile organic compounds, among them benzene is the most important, because their toxicological significance. Benzene is a myelotoxic agent, carcinogenic and classified as Group I by the International Agency of Research on Cancer (IARC). Their interaction with DNA molecules can indicate an early injury allowing to establish measures to protect the health of the exposed population. The comet assay is a highly sensitive method for detecting DNA damage induced by environmental or occupational exposure to mutagens. The aim of this study was to validate the comet test using gama irradiation to measure genotoxic damage induced in peripheral blood lymphocytes, in addition to evaluating occupational exposure to benzene in gasoline by analysis and comparison of this biomarker and biomarker of benzene exposure - trans, trans muconic acid (ttMA). The comet assay showed that the Index Damage (ID) of the exposed group (28.4 ± 10.1) was significantly higher in the control group (18.4 ± 10.1), as well as the values of urinary ttMA were significantly higher in the exposed group (1.13 ± 0.45> 0.44 ± 0.33). Moreover, the values urinary ttMA showed a good correlation with the rate of DNA damage (K> 0.70). Occupational exposure related fuels can cause an increased risk of genetic damage among individuals in this sector is therefore of paramount importance that analysis to study the health risks, in addition to being a strategic tool to improve the safety and quality of life for workers.